Psychos 4 movie midnight marathon pack. - Franklin, Richard, 1948-2007.; Perkins, Anthony, 1932-1992.; Miles, Vera.; Loggia, Robert; Tilly, Meg.; Scarwid, Diana, 1955-; Fahey, Jeff.; Maxwell, Roberta, 1942-; Garris, Mick.; Hussey, Olivia; Pounder, C. C. H.; Frost, Warren; et al. (Universal City, CA : Universal Studios Home Entertainment, 2014)
Psycho II (1983, 113 min.): After years of treatment at a mental institution for the criminally insane, Norman Bates still can't quite elude the demands of "Mother."
Psycho III (1986, 93 min.): A failed nun and a sleazy musician find the desert motel Norman Bates runs in memory of his mother.
Psycho IV: the beginning (1990, 97 min.): When Norman Bates is drawn to a late night radio show where he shares his views on the topic of matricide, he relives his trials as a young boy living with his widowed schizophrenic mother. These haunting memories threaten to rekindle his killing urge.
Bates Motel (1987, 96 min.): A mentally disturbed man who roomed with the late Norman Bates at the state lunatic asylum inherits the legendary Bates Motel after Norman's death and tries to fix it up to make it a respectable business.
Psycho II -- Psycho III -- Psycho IV: the beginning -- Bates Motel.
Psycho II: directed by Richard Franklin.
Psycho III: directed by Anthony Perkins.
Psycho IV: the beginning: directed by Mick Garris.
Bates Motel: directed by Richard Rothstein.
Psycho II: Anthony Perkins, Vera Miles, Robert Loggia, Meg Tilly.
Psycho III: Anthony Perkins, Diana Scarwid, Jeff Fahey, Roberta Maxwell.
Keywords: Bates, Norman -- (Fictitious character); Mental illness -- Drama; Murder -- Drama; Fiction films; Drama; Feature films; Horror films